Comparative Analysis of Cash Management Internal Controls in the Selected DepEd Schools Division in the Province of Albay, Philippines - Alcera, Aily A. (The Indonesian Institute of Science and Technology Research, 2026)
The research sought to evaluate and strengthen the Cash Management Internal Controls (CMICs) within the Department of Education (DepEd) Region V. Using a descriptive‑evaluative, explanatory sequential mixed‑methods design, the study evaluated financial practices, regulatory compliance, and operational challenges across selected school division offices and implementing units. Findings revealed a highly effective and consistently compliant internal control environment, characterized by strong clerical performance and strict adherence to national standards such as UACS coding. Core strengths included clear authorization hierarchies and pre‑audit functions, which achieved near‑perfect evaluative scores. However, a significant infrastructure–process gap emerged: While bookkeeping was accurate, the organization remained operationally exposed due to inadequate physical safeguards, including the lack of fireproof vaults and secure transport vehicles. The study also identified a digital‑infrastructure paradox wherein high staff competency was undermined by external systemic risks, including poor internet connectivity, delays in the release of Notices of Cash Allocation (NCAs), and administrative capacity gaps that led to process fatigue. These bottlenecks correlate with the receipt of Audit Observation Memoranda (AOMs) received. Recommendations focused on shifting from primarily administrative training to capital investment. Key proposals included procuring secure logistics and fireproof storage, hiring additional administrative support, and fully transitioning to the Budget and Treasury Management System (BTMS) to automate reconciliations and enhance long‑term financial efficiency.